(untitled) (Nonlinear Studies, 2023)
We examine the existence and uniqueness of a mild solution to the semilinear impulsive fractional integro-differential system [SIFIDS] through conformable derivative [] in Banach spaces. To do this, we work through the system in stages and use the method of semigroup of operators in conjunction with the Banach contraction principle. In the latter section of the study, a numerical example is provided to demonstrate the application of the theoretical ideas presented.